2017
DOI: 10.1002/pen.24682
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection molding of polypropylene/multi‐walled carbon nanotube nanocomposites: The influence of process parameters

Abstract: Polypropylene (PP) filled with 10 wt% multi‐walled carbon nanotube (CNT) nanocomposites were prepared via masterbatch dilution and subjected to microinjection molding (μIM) under various processing conditions. The molding conditions were altered by systematically changing the machine variables, such as: melt temperature, mold temperature, backpressure and injection velocity. A mold insert with a three‐step decrease in thickness along the flow direction was adopted. The effect of molding parameters on the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…The FD σ for both the thick and middle sections of microparts is higher than the TD σ of corresponding counterparts, which indicates a role for the preferential orientation of conductive fillers along the melt FD. A similar trend has been observed for their CNT‐containing PP counterparts .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FD σ for both the thick and middle sections of microparts is higher than the TD σ of corresponding counterparts, which indicates a role for the preferential orientation of conductive fillers along the melt FD. A similar trend has been observed for their CNT‐containing PP counterparts .…”
Section: Resultsmentioning
confidence: 99%
“…Pan et al reported that the cooling time drops dramatically with a reduction of mold cavity thickness. Therefore, it is anticipated that the generated structure in the thin section (0.2 mm) can instantly “freeze” and have little chance returning to a random orientation . In this scenario, the TD σ for the thin section of corresponding microparts can be substantially reduced due to a lack of sufficient conductive pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation of CNT is enhanced with the increasing shearing effect in the melt filling direction, arising from the combined effects of higher injection speed and convergence of mold cavities in flow direction . In a recent study, Zhou et al found that an increase of melt temperature and mold temperature is advantageous to the enhancement of electrical conductivity ( σ ) in subsequent polypropylene (PP)/CNT microparts. Moreover, the morphology observations indicated that CNT achieved a relatively uniform dispersion in PS, whereas the appearance of CNT aggregates was detected in PP .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Zhou et al found that an increase of melt temperature and mold temperature is advantageous to the enhancement of electrical conductivity ( σ ) in subsequent polypropylene (PP)/CNT microparts. Moreover, the morphology observations indicated that CNT achieved a relatively uniform dispersion in PS, whereas the appearance of CNT aggregates was detected in PP . Thus, the melt and mold temperatures are important process parameters, which determine the microstructure of polymer nanocomposites in μIM.…”
Section: Introductionmentioning
confidence: 99%